2018
DOI: 10.3389/fped.2018.00118
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Overload and Renal Angina Index at Admission Are Associated With Worse Outcomes in Critically Ill Children

Abstract: Objectives: We investigated the association of fluid overload and oxygenation in critically sick children, and their correlation with various outcomes (duration of ventilation, ICU stay, and mortality). We also assessed whether renal angina index (RAI) at admission can predict mortality or acute kidney injury (AKI) on day 3 after admission.Design and setting: Prospective study, pediatric intensive care in a tertiary hospital.Duration: June 2013-June 2014.Patients: Patients were included if they needed invasive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…There have been multiple studies on the validation of RAI in critical children. In an earlier study from India, we demonstrated that RAI was better than traditional markers of AKI and illness severity scores with high AUC in RAI ≥8, and higher negative predictive values for RAI <8 [8]. The study [9], published in the current issue of Indian Pediatrics, adds on to the evidence that day 0 RAI has a good sensitivity, specificity, and negative predictive value for AKI on day 3 of admission.…”
Section: Risk Stratification For Acute Kidney Injury In Critically-ilmentioning
confidence: 68%
“…There have been multiple studies on the validation of RAI in critical children. In an earlier study from India, we demonstrated that RAI was better than traditional markers of AKI and illness severity scores with high AUC in RAI ≥8, and higher negative predictive values for RAI <8 [8]. The study [9], published in the current issue of Indian Pediatrics, adds on to the evidence that day 0 RAI has a good sensitivity, specificity, and negative predictive value for AKI on day 3 of admission.…”
Section: Risk Stratification For Acute Kidney Injury In Critically-ilmentioning
confidence: 68%
“…The current study data provide evidence of safety for DCC from a kidney perspective in VLBW infants who typically have an AKI rate of 29% during their NICU hospitalization. 10 With recent evidence from pediatric studies that fluid overload increases the risk of AKI 15 and with DCC providing nearly an equivalent of a blood transfusion, this is an important addition to the safety profile of DCC that has not been analyzed in prior studies.…”
Section: Discussionmentioning
confidence: 99%
“…Volume resuscitation in hemodynamically unstable patients is one of the most commonly used therapeutic options. Nevertheless, excessive uid administration may impair tissue perfusion even further by promoting edema and third-space uid accumulation [6,7,60]. A rise in cardiac output (or stroke volume) as a result of volume resuscitation is called uid responsiveness.…”
Section: Volume Resuscitation and Uid Responsivenessmentioning
confidence: 99%
“…However, the optimal way to resuscitate children with circulatory failure is controversial. The exact order and quantity of uids or vasoactive drug administration in the critically-ill child with shock is supported by little evidence, although there are several consensus statements [4,5] Overzealous uid resuscitation is detrimental to some children [6,7]. There is some consensus regarding the rst-line treatment in patients with shock or signi cant hemodynamic instability, but debate remains concerning how much uid should be administered, which type of vasoactive drug should be used, how to assess the hemodynamic changes and ultimately what hemodynamic clinical goal should be targeted to guide optimal treatment.…”
Section: Introductionmentioning
confidence: 99%